On Parr: The Use and Propriety of Appraisal Methods in Computing Fracking Awards - Goldberg, Hilary M.; Calnan, Ray (Journal of Law and Commerce, 2017)
Parr v. Aruba Petroleum, Inc. made headlines in 2014 for being the first hydraulic fracturing (“fracking”) case to result in a jury verdict. In Parr, a Texas jury awarded $2.925 million to compensate the Parr family for injuries sustained as a result of Aruba Petroleum’s nearby fracking activities. Of the nearly $3 million verdict, the jury awarded $275,000 for diminution in property value. Thanks to the fiercely litigated and highly publicized trial and appeal, scholars, practitioners and academics received a rare glimpse into an area of litigation otherwise insulated from public view by out of court resolutions and confidential settlement agreements. In this interdisciplinary paper we will provide an overview of the valuation process, addressing issues specific to diminution in value in the context of fracking and similar incidences of environmental contamination. We will then explain the various appraisal methods within the context of real estate litigation, including the Sales Comparison Approach, Income Approach and Cost Approach. Using Parr as a test case, we will then analyze the unique appraisal challenges presented by the hydraulic fracturing and analogous toxic torts fact patterns, evaluating the probative value and persuasive necessity of each approach. Finally, we will make predictions about the rapidly evolving fracking litigation sphere, analyzing new challenges presented to homeowners, energy companies and the judiciary when faced with allegations of diminished property values.